Comparison of American Binomial Options with Discrete and Continuous Dividend - Dian Ayu Merdekawati; Yolanda Norasia; Charisma Juni Kumalasari; Endah Rokhmati Merdika Putri (LPPM Institut Teknologi Sepuluh Nopember, 2020)
This study discusses the effect of dividend on option pricing by using a binomial method. It also investigated the initial stock value, number of steps, and strike price effects on the behavior of options pricing. From several simulations conducted, it was found that the values of call options with discrete dividend are greater than the continuous dividend. While on the put option, the values of the put options with a continuous dividend are greater than the discrete dividend.